Haiti : Staff-Monitored Program-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept.. (Washington, D.C. : International Monetary Fund, 2022)
Since 2018, Haiti has experienced a protracted political crisis, repeated country lock-downs and civil unrest, an earthquake, the assassination of its president and a deep recession. Policymakers face economic imbalances, a surge in gang violence, worsening poverty conditions, and dire social challenges aggravated by years of political instability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Haiti